The Molecular Imaging of Natural Killer Cells - Mariya Shapovalova; Sean R. Pyper MD, PhD; Branden S. Moriarity PhD; Aaron M. LeBeau PhD (Molecular Imaging)
The recent success of autologous T cell-based therapies in hematological malignancies has spurred interest in applying similar immunotherapy strategies to the treatment of solid tumors. Identified nearly 4 decades ago, natural killer (NK) cells represent an arguably better cell type for immunotherapy development. Natural killer cells are cytotoxic lymphocytes that mediate the direct killing of transformed cells with reduced or absent major histocompatibility complex (MHC) and are the effector cells in antibody-dependent cell-mediated cytotoxicity. Unlike T cells, they do not require human leukocyte antigen (HLA) matching allowing for the adoptive transfer of allogeneic NK cells in the clinic. The development of NK cell-based therapies for solid tumors is complicated by the presence of an immunosuppressive tumor microenvironment that can potentially disarm NK cells rendering them inactive. The molecular imaging of NK cells in vivo will be crucial for the development of new therapies allowing for the immediate assessment of therapeutic response and off-target effects. A number of groups have investigated methods for detecting NK cells by optical, nuclear, and magnetic resonance imaging. In this review, we will provide an overview of the advances made in imaging NK cells in both preclinical and clinical studies.